Implementasi Aplikasi TOEFL Learning English dalam Meningkatkan Kesiapan TOEFL Peserta Pelatihan - Akhmad Sayuti; Nurlista Iryanti; Irwansyah Irwansyah; Bella Paramita; Dora Indah Triana (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
English language proficiency, measured through the Test of English as a Foreign Language (TOEFL), is an important competency in the academic and professional world. However, many training participants still experience difficulties in preparing for the TOEFL test due to limited effective and flexible learning methods. This Community Service Activity aims to implement the TOEFL Learning English Application as a digital-based learning medium to improve the TOEFL readiness of training participants. The implementation method includes the preparation stage, application usage training, mentoring, and evaluation through TOEFL pre-tests and post-tests. The results of the activity show an increase in the TOEFL readiness of training participants, marked by an increased understanding of listening, structure, and reading comprehension materials as well as increased participant confidence in facing the TOEFL test. The implementation of the TOEFL Learning English application also contributes to improving digital literacy and learning independence of participants. Thus, the use of the TOEFL Learning English application can be an alternative solution for effective, practical, and sustainable TOEFL learning in training and community service activities.